Vidro de spin e antiferromagnetismo com interacão de pareamento BCS local - Kipper, Carla Judite (2005)
In this work the competition among spin glass(SG), antiferromagnetism (AF) and BCS pairs formation (PAIR) in real space is investigated. The model consists of an Ising spin glass term and a local BCS term that favors double site occupation. This model is composed by two sublattices, but only spins in diferent sublattices can interact. The Ising coupling is a random variable Jij that follows a gaussian probability distribution with average - J0=N and variance J²=N. The problem is formulated in terms of functional integral formalism, where the spin operators are written as bilinear combination of Grassmann felds. Using the replica method and the static approach for the spin-spin correlation functions, we obtain the grandcanonical potential. The results are presented in phase diagrams which show T=J versus g=J for several values of J0=J (where T is the temperature and g is the pairing strength interaction). The order parameters solution indicate the PAIR phase (double ocupation of sites) when g=J is sufciently high. As the value of g=J decreases, the problem presents antiferromagnetic or spin glass solution, that dependis on the ratio J0=J. For high temperatures and any value of J0, we obtain paramagnetic solution. For values of J0 ≤ 1:5J, the SG solution appears at temperature Tf = 0:96J. In the range 1:5J < J0 ≤ 1:7J, the AF phase appears between the paramagnetic and spin glass solutions. The spin glass solution is not found when J0 > 1:7J.